2017
DOI: 10.12693/aphyspola.132.1145
|View full text |Cite
|
Sign up to set email alerts
|

Production of Barite and Boroncarbide Doped Radiation Shielding Polymer Composite Panels

Abstract: Developments in nuclear technology in the last century have lead to the use of radiation in different areas of human activity. These are not just the energetics but also food, agriculture, medicine, industry and science. Thus, radiation has become an inevitable phenomenon in our lives. Since we cannot isolate radiation from our life, the radiation protection methods should be available. As alternatives to conventional radiation prevention methods, such as lead and heavy concrete shielding, more functional mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…As shown in Fig. 6 (Dinçer 2018;Strydom et al 1995). Figure 6 shows that patterns of pure barite powders are present in the XRD patterns, similar to the results from the literature (Evcin et al As shown in Table 3 and Fig.…”
Section: Resultssupporting
confidence: 85%
“…As shown in Fig. 6 (Dinçer 2018;Strydom et al 1995). Figure 6 shows that patterns of pure barite powders are present in the XRD patterns, similar to the results from the literature (Evcin et al As shown in Table 3 and Fig.…”
Section: Resultssupporting
confidence: 85%
“…Graphite/epoxy composite showed the highest performance in gamma radiation attenuation among epoxy/graphite, epoxy/lead, and epoxy/boron (Saiyad et al 2014 ). A proportional relationship between photon attenuation coefficients and barite concentration was revealed when barite and boron carbide-doped radiation shielding polymer composite was prepared for radiation shielding (Evcın et al 2017 ). Blended powdered polyethylene glycol and lead oxide prepared by physical mixing revealed that the shielding properties of polyethylene glycol increased with the addition of lead oxide (Hussain et al 1997 ).…”
Section: Polymer Composites For Gamma-radiation Shieldingmentioning
confidence: 99%
“…Now, they are very important factors for the processability of an RSF. The durability and organization between a shield material and the process technology have been studied [17,18]. For RSFs in the industrial field, an important condition for the safe transfer of contaminated substances after the Fukushima incident in Japan was that the minimum strength should support the weight.…”
Section: Discussionmentioning
confidence: 99%